Novel insights related to the rise of KPC-producing Enterobacter cloacae complex strains within the nosocomial niche - Knecht, Camila A.; García Allende, Natalia; Álvarez, Verónica E.; Prack McCormick, Barbara; Massó, Mariana G.; Piekar, María; Campos, Josefina; Fox, Bárbara; Camicia, Gabriela; Gambino, Anahí S.; Leguina, Ana Carolina del Valle; Donis, Nicolás; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
According to the World Health Organization, carbapenem-resistant Enterobacteriaceae (CRE) belong to the highest priority group for the development of new antibiotics. Argentina-WHONET data showed that Gram-negative resistance frequencies to imipenem have been increasing since 2010 mostly in two CRE species: Klebsiella pneumoniae and Enterobacter cloacae Complex (ECC). This scenario is mirrored in our hospital, with K. pneumoniae accounting for 85% of carbapenem-resistant strains, and in second place the ECC with 12%. We aimed to contribute to the understanding of the rise of ECC in Argentina, taking as a biological model both a patient colonized with two KPC-producing strains (one Enterobacter hormaechei and one K. pneumoniae) and in vitro competition assays with prevalent KPC-producing ECC (KPC-ECC) versus KPC-producing K. pneumoniae (KPC-Kp) high-risk clones from our institution. A KPC-producing E. hormaechei strain that belonged to the pandemic lineage ST45 (HA2pEho), and later a KPC-Kp strain which belonged to ST18 (HA7pKpn) were colonizing the same patient. Both strains were MDR and shared a novel conjugative IncM1 plasmid (77.2 Kb) with blaKPC-2 embedded in the genetic platform ISKpn27-blaKPC-2-ISKpn6-HP-Tn3. In addition, a total of 19 KPC-ECC and 58 KPC-Kp strains isolated from nosocomial infections from 10/2018 until 12/2020 in our institution were sequenced. International high-risk clones KPC-Kp ST11 and ST258 as well as KPC-ECC ST66 and ST78 were found and tested in competition assays. The competition assays with KCP-ECC ST45, ST66, and ST78 versus KPC-Kp ST11, ST18, and ST258 strains analysed here showed no statistically significant difference between them. These assays evidenced that high-risk clones of KPC-ECC and KPC-Kp can coexist in the same hospital environment including the same patient. These findings offer hints to explain the worldwide rise of KPC-ECC strains based on the ability of some pandemic clones to compete and occupy a certain niche. Both the presence of the same new plasmid, and the fitness results that showed that both strains can coexist within the same patient suggest that horizontal genetic transfer of blaKPC-2 within the patient cannot be ruled out. As a whole, these findings highlight the constant interaction that these two species have in the hospital environment.